2011
DOI: 10.1007/s00216-011-5543-9
|View full text |Cite
|
Sign up to set email alerts
|

Study of the naphthalene-2,3-dicarboxaldehyde pre-column derivatization of biogenic mono- and diamines in mixture and fluorescence−HPLC determination

Abstract: A new fluorescence-HPLC method was developed for the simultaneous determination of eight biogenic monoamines (histamine, methylamine, tyramine, ethylamine, propylamine, tryptamine, 2-phenylethylamine, isoamylamine) and two biogenic diamines (putrescine, cadaverine) in the presence of heptylamine as the internal standard. The amines were pre-column derivatized with naphthalene-2,3-dicarboxaldehyde in the presence of cyanide ion as the nucleophile. The effect of the derivatization reaction conditions on the reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 61 publications
(71 reference statements)
1
10
0
Order By: Relevance
“…The maximum derivatization yields were obtained when 2.5 mM NDA and 2.5 mM NaCN were used. A decrease in derivatization yields was observed with higher concentrations of NaCN, which is in agreement with the literature .…”
Section: Resultssupporting
confidence: 92%
“…The maximum derivatization yields were obtained when 2.5 mM NDA and 2.5 mM NaCN were used. A decrease in derivatization yields was observed with higher concentrations of NaCN, which is in agreement with the literature .…”
Section: Resultssupporting
confidence: 92%
“…Previous published works reported that NDA could be dissolved both in acetonitrile or methanol, without detailing if a contribution of the solvent in the derivatizing reaction is present [17,32].…”
Section: Effect Of Initial Nda Concentrationmentioning
confidence: 99%
“…Numerous methods, such as chromatography (LC, HPLC, GC, and ion exchange), electrophoretic techniques, fluorescence, and UV–Vis spectroscopy (Khuhawar and Qureshi, 2001 ; Reinemann et al, 2009 ; Zotou and Notou, 2012 ; Mohammed et al, 2016 ; Sun et al, 2017 ), have been reported for BA detection. Furthermore, based on selective recognition through non-covalent interactions between a receptor unit and an analyte, the supramolecular-complex method has been used to identify BAs.…”
Section: Introductionmentioning
confidence: 99%